Control of breast cancer patient-derived xenografts by CD70-targeted HIT-CAR T cells - Pieter L. Lindenbergh; Vinagolu K. Rajasekhar; Irina Linkov; Jorge Mansilla-Soto; Sophie A. Hanina; Michel Sadelain (Frontiers in Immunology, 2026)
CAR T cell therapies have shown clinical success in several tumor types, though not in breast cancer, for which advanced stages remain incurable. CD70 is expressed in a broad range of solid tumor types and is emerging as a molecular target for CAR T cells in renal and ovarian malignancies. Here we show that a subset of breast cancer cell lines and patient-derived xenografts express CD70, albeit to varying levels. Leveraging a recently developed HLA-independent T cell (HIT) receptor with greater sensitivity to CD70 than conventional CAR designs, we assessed whether CD70 can be targeted to eliminate breast cancer cells. We observed that CD70-targeted HIT T cells showed antigen-specific activation in vitro , and cytotoxicity against breast cancer cell lines and patient-derived xenograft cells across a broad range of CD70 levels. Implanted in the murine mammary fat pad, high CD70-expressing patient-derived xenografts were readily eliminated by both conventional CAR and HIT T cells. Against xenografts with lower CD70 expression, however, CD70-targeted HIT T cells engineered with supplemental costimulation outperformed conventional CAR T cells by inhibiting tumor outgrowth in mice, and conferred a significant survival benefit. These findings establish that CD70 is a targetable antigen in breast cancer and highlight the potential of enhanced-sensitivity receptor designs such as HIT receptors to engage a broader range of tumors.